2022
DOI: 10.1038/s41598-021-04200-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent atmospheric changes and future projections along the Saudi Arabian Red Sea Coast

Abstract: Recent and future climate diagrams (surface air temperature, surface relative humidity, surface wind, and mean sea level pressure) for the Saudi Arabian Red Sea Coast are analysed based on hourly observations (2016–2020) and hourly ERA5 data (1979–2020) with daily GFDL mini-ensemble means (2006–2100). Moreover, GFDL mini-ensemble means are calculated based on the results of three GFDL simulations (GFDL-CM3, GFDL-ESM2M, and GFDL-ESM2G). Observation data are employed to describe the short-term current weather va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies in Asia have deduced that ERA5 (hereafter ERA) outperforms other existing reanalysis and gridded products for hydroclimatic applications 42,43 . This dataset have also been used in climate studies pertaining to the AP 44,45 . In this study, we used the ERA precipitation and near-surface temperature (mean, minimum, and maximum) for the period 1951-2020.…”
Section: Datasetsmentioning
confidence: 99%
“…Several studies in Asia have deduced that ERA5 (hereafter ERA) outperforms other existing reanalysis and gridded products for hydroclimatic applications 42,43 . This dataset have also been used in climate studies pertaining to the AP 44,45 . In this study, we used the ERA precipitation and near-surface temperature (mean, minimum, and maximum) for the period 1951-2020.…”
Section: Datasetsmentioning
confidence: 99%
“…Interactions between the GCM and RCM can also be important in Central Europe in the case of summer precipitation. Bawadekji et al (2022) made a bias-correction for the 2006-2020 control period under four different RCP scenarios (RCP2.6, RCP4.5, RCP6.0, RCP8.5), but the effect of the bias-correction was similar regardless of the applied scenario. Coppola et al (2021) analysed a large ensemble of EURO-CORDEX simulations and found that the greatest variability between models in the case of precipitation occurs in Central Europe.…”
Section: Introductionmentioning
confidence: 99%